Studi Literasi Taksonomi dan Penelusuran Spesimen Lektotipe Cengkih (Syzygium aromaticum (L.) Merr. & Perry) - Suparman Suparman; Nurhasanah Nurhasanah; Bahtiar Bahtiar; Sri DAS (TECHNO: JURNAL PENELITIAN, 2020)
Old scientific names of clove, Caryophyllus aromaticus, was published in 1753 by Carrolus Linnaeus and up to now it has many synonyms. Now, the old name is still recognized as basionim of clove. Merrill & Perry, based on the character, subsequently revised the genus of clove from the Caryophyllus to Syzygium, so the accepted scientific name is Syzygium aromaticum. The lectotype specimen was designed by McVaugh in 1989 and stored in BM from the Clifford collection.